Hydroxysafflor Yellow A: A Systematical Review on Botanical Resources, Physicochemical Properties, Drug Delivery System, Pharmacokinetics, and Pharmacological Effects - Zhao, Feng; Wang, Ping; Jiao, Yuanyuan; Zhang, Xiaoxiao; Chen, Daquan; Xu, Haiyu (Frontiers in Pharmacology, 2020)
Hydroxysafflower yellow A (HSYA), as a principal natural ingredient extracted from safflower (Carthamus tinctorius L.), has significant pharmacological activities, such as antioxidant, anti-inflammatory, anticoagulant, and anticancer effects. However, chemical instability and low bioavailability have been severely hampering the clinical applications of HSYA during the treatment of cardiovascular and cerebrovascular disease. Therefore, this present review systematically summarized the materials about HSYA, including obtain methods, extraction and detection methods, pharmacokinetics, pharmacological effects and molecular mechanism, especially focus on the possible causes and resolutions about the chemical instability and low bioavailability of HSYA, in order to provide relatively comprehensive basic data for the related research of HSYA.